Citizenship in the Classical Islamic Political Thought According to the Charter of Medina - Abid, Hayat; Bioud, Mohamed Ali (Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
The Constitution of Medina, also known as The Charter of Medina was considered as the first and oldest political document in the Islamic political thought. It was regarded as the first written constitution for the Islamic state established by Prophet Muhammad after the Hijra (migration). The document recorded various identities, nationalities and religions organized by Islamic government based onseveralprinciples. This study tried to analyze the document according to its form, contents, and historical background. Also, the principles mentioned in the document, whether it was political, constitutional, human rights or judiciary field. The standard of citizenship in the Constitution of Medina was written based on the country apart from language or beliefs diversities. This study invites a deeper search for the prophetic documents to rediscovery the Islamic political thoughts and its context to the contemporary Islamic political discourse.